2005
DOI: 10.1007/s10705-004-7358-y
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improved Coefficients for Predicting Direct N2O Emissions from Soil in Canadian Agroecosystems

Abstract: Agricultural soils emit nitrous oxide (N 2 O), a potent greenhouse gas. Predicting and mitigating N 2 O emissions is not easy. To derive national coefficients for N 2 O emissions from soil, we collated over 400 treatment evaluations (measurements) of N 2 O fluxes from farming systems in various ecoregions across Canada. A simple linear coefficient for fertilizer-induced emission of N 2 O in non-manured soils (1.18% of N applied) was comparable to that used by the Intergovernmental Panel on Climate Change (IPCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 66 publications
9
68
1
Order By: Relevance
“…N 2 O emissions originating from sources other than soybean crop residue decomposition (i.e., soil N) have been estimated as 0.405 kg N ha −1 yr −1 (Helgason et al 2005). Most of the previous studies presented in Table 1 did not separately measure N 2 O emissions from residues and emissions from soil organic matter (background emissions).…”
Section: Nodule Decomposition In Soybeans and N 2 O Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…N 2 O emissions originating from sources other than soybean crop residue decomposition (i.e., soil N) have been estimated as 0.405 kg N ha −1 yr −1 (Helgason et al 2005). Most of the previous studies presented in Table 1 did not separately measure N 2 O emissions from residues and emissions from soil organic matter (background emissions).…”
Section: Nodule Decomposition In Soybeans and N 2 O Emissionsmentioning
confidence: 99%
“…Most of the previous studies presented in Table 1 did not separately measure N 2 O emissions from residues and emissions from soil organic matter (background emissions). Thus, we assumed the background N 2 O emissions from the value reported by Helgason et al (2005) and from the measurement period. In Table 1, in the "Total N 2 O emissions" column, the values were expressed as "the cumulative N 2 O emissions from soil surface after the harvest minus the estimated background N 2 O emissions" using the value reported by Helgason et al (2005).…”
Section: Nodule Decomposition In Soybeans and N 2 O Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chatskikh and Olesen (2007) suggested that the greater N 2 O emissions under no-till treatments may be due to reduced gas diffusivity and air-filled porosity, often caused by high soil moisture, which favours the activity of denitrifying bacteria. Helgason et al (2005) analysed N 2 O emissions in Canada using over 400 datasets from a range of farming management regimes, including tillage practices, and found that no-till treatment increased N 2 O emissions in humid climates but decreased it in semiarid climates. In the USA, Six et al (2004) found that the conversion from conventional to no-till practice had a strong time dependency on N 2 O emissions in both humid and dry climates, demonstrating that greenhouse gas mitigation by adoption of no-till technology is much more variable and complex than previously considered.…”
Section: Introductionmentioning
confidence: 99%
“…VWC and WFP for the Lower Longley, Lucaston and the inter-row at Young showed an atypical significant negative (weak) influence on N 2 O emissions. Elevated emissions are linked to WFP > 60% (Chantigny et al 1998;Helgason et al 2005) and VWC > 0.55 cm 3 cm -3 (van der Weerden et al 2012), conditions rarely seen in the orchards during the study period. For these sites, during winter when WFP and VWC were highest, soil temperatures were extremely low and accounted for the negative correlation observed and the moderately negative correlation between VWC and N 2 O emissions in winter (r = -0.506).…”
Section: Temporal and Spatial Variability Of N 2 O Emissionsmentioning
confidence: 99%